Formaldehyde and nitrogen dioxide over the remote western Pacific Ocean: SCIAMACHY and GOME-2 validation using ship-based MAX-DOAS observations - Peters, Enno; Großmann, Katja; Frieß, Udo (Atmospheric chemistry and physics. Discussions, 2012)
Abstract. In October 2009, shipborne Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements were performed during the TransBrom campaign over the western Pacific Ocean (≈ 40° N to 20° S). Vertical tropospheric trace gas columns and profiles of nitrogen dioxide (NO2) and formaldehyde (HCHO) as well as stratospheric NO2 columns were retrieved in order to validate corresponding measurements from the GOME-2 and SCIAMACHY satellite instruments and to estimate tropospheric background concentrations of these trace gases. All instruments reproduced the same characteristic, latitude-dependent shape of stratospheric NO2. SCIAMACHY and GOME-2 data differ by about 1% from each other while yielding lower vertical columns than MAX-DOAS morning values as a consequence of measurement time and stratospheric NO2 diurnal cycle. Due to this diurnal cycle, an increase of 8.7 ± 0.5 × 1013 molec cm−2 h−1 of stratospheric NO2 was estimated from MAX-DOAS data at low latitudes during the day. Tropospheric NO2 was above the detection limit only in regions of higher anthropogenic impact (ship traffic, transport of pollution from land). A background column of 1.3 × 1014 molec cm−2 (or roughly 50 ppt boundary layer concentration) can be estimated as upper limit for the remote ocean, which is in agreement with GOME-2 monthly mean values. In the marine boundary layer close to the islands of Hokkaido and Honshu, up to 0.8 ppbv were retrieved close to the surface. Background HCHO concentrations over the remote ocean exhibit a diurnal cycle with maximum values (depending strongly on weather conditions) of 4 × 1015 molec cm−2 for the vertical column at noontime. Corresponding peak concentrations of up to 1.1 ppbv were retrieved in elevated altitudes (≈ 400 m) around noon while maximum concentrations in the evening are close to the ground. An agreement between MAX-DOAS and GOME-2 data was found for typical vertical columns of 3 × 1015 molec cm−2 over the remote ocean at the time of overpass.
Gesehen am 26.07.2018